2021
DOI: 10.1038/s42003-020-01541-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals sex determination and liver high-fat storage mechanisms of yellowstripe goby (Mugilogobius chulae)

Abstract: As a promising novel marine fish model for future research on marine ecotoxicology as well as an animal model of human disease, the genome information of yellowstripe goby (Mugilogobius chulae) remains unknown. Here we report the first annotated chromosome-level reference genome assembly for yellowstripe goby. A 20.67-cM sex determination region was discovered on chromosome 5 and seven potential sex-determining genes were identified. Based on combined genome and transcriptome data, we identified three key lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…Therefore, we speculate that the shimofuri goby genome belongs to the common diploid genome. The size of the shimofuri goby genome (887.60 Mb) was similar to that of the most published species of Gobiidae, being smaller than those of Boleophthalmus pectinirostris (955.75 Mb) and Mugilogobius chulae (1003.36 Mb) [33,34]. Differences in genome size may be due to the differences in repeat sequence content and transposon insertion events [35].…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, we speculate that the shimofuri goby genome belongs to the common diploid genome. The size of the shimofuri goby genome (887.60 Mb) was similar to that of the most published species of Gobiidae, being smaller than those of Boleophthalmus pectinirostris (955.75 Mb) and Mugilogobius chulae (1003.36 Mb) [33,34]. Differences in genome size may be due to the differences in repeat sequence content and transposon insertion events [35].…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, genomic data provides a foundation for comparative studies, helping identify unique adaptations, ecological interactions, and evolutionary innovations. While many gobioid genome assemblies have been generated recently (Adrian-Kalchhauser et al, 2020; Cai et al, 2021; Y. Hu et al, 2021; Q.…”
Section: Introductionmentioning
confidence: 99%
“…The sh liver, as a target tissue that regulates lipid metabolism, plays a vital role in lipid digestion and absorption (Harvey et al, 2019). Current research has shown that there are multiple factors affecting lipid deposition in sh liver, including diets (Zhou et al, 2023;Ji et al, 2022), environment (Zhou et al, 2019), physiology (Cai et al, 2021), and species (Ando et al, 1993). Studies on grass carp have reported that a high-lipid diet (with a lipid level of 8.8%) induces lipid accumulation in the hepatopancreas (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%